A case report of 26 weeks of complete molar pregnancy with posterior uterine fibroid - Prabhakar, Manju; Ali, Maryam (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Molar pregnancy is one of the classifications of GTD and sometimes can be associated with hyperthyroidism. The classic features are irregular vaginal bleeding, hyper emesis and large uterus for gestational age. Though incidence of uterine fibroid with pregnancy is 1% to 10% but encountered with molar pregnancy is rare. Here we reported a case of complete molar pregnancy with posterior uterine fibroid who initially presented with 3-month amenorrhea and had a complaint of spotting per vagina occasionally with ultrasonography report suggestive of molar pregnancy and post uterine fibroid with raised beta-hCG with low TSH suggestive of hyperthyroidism.